Intermolecular bonding in C70 at high pressure and temperature. (December 2017) - Sundqvist, Bertil
Abstract: Near-infrared (NIR) Raman spectroscopy has been used to analyze intermolecular bonding in solid C70, treated for 2 h under pressures in the range 0.8–2 GPa at temperatures between 350 and 600 K. The spectra obtained are analyzed in detail with the aim of finding spectral lines characteristic for the monomer C70, the dimer C140, and possibly for higher oligomers. In agreement with earlier studies, several new modes are observed in the NIR Raman spectra, in sharp contrast to what is found in Raman studies using visible light excitation. From the relative intensities of the characteristic dimer stretch line at 88 cm −1 and a mode at 457 cm −1, characteristic for the monomer, a semi-quantitative estimate for the dimer fraction in the material can be found as a function of pressure and temperature. From these results a reaction map, similar to that recently derived for C60, can be drawn. The data obtained indicate that C70 is almost completely polymerized into large, random oligomers (or polymers) after long-time treatment at elevated temperatures (>500 K) and pressures (>1.2 GPa). The phase diagram of C70 is updated and briefly discussed in the light of this and other recent high pressure studies. Graphical abstract: